2014
DOI: 10.1155/2014/179648
|View full text |Cite
|
Sign up to set email alerts
|

Mild Cognitive Impairment and Depressive Symptoms in Elderly Patients with Diabetes: Prevalence, Risk Factors, and Comorbidity

Abstract: The aim of the study was to estimate the prevalence of mild cognitive impairment (MCI), depressive syndrome cases, and its comorbidity, and to identify predictors of these conditions. Methods. 276 diabetics elders were screened for MCI and depressive symptoms. Detailed information of history of diabetes, and data of BMI, HbA1c, and blood lipids were collected. Results. The prevalence of MCI was 31.5%, depressive syndrome was 29.7%, and MCI with coexisting depressive mood was 9.1%. The logistic regression analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
63
6
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 30 publications
5
63
6
1
Order By: Relevance
“…Studies in patients with type 2 diabetes detected MCI in about one third of participants through cognitive screening and an assessment of activities of daily living (ADL) and instrumental ADL [29,30] . Finally, multiple studies have assessed cognition in patients with CHF.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in patients with type 2 diabetes detected MCI in about one third of participants through cognitive screening and an assessment of activities of daily living (ADL) and instrumental ADL [29,30] . Finally, multiple studies have assessed cognition in patients with CHF.…”
Section: Discussionmentioning
confidence: 99%
“…Higher levels of HbA1c, diagnosis of CVD and hypertension, increased number of co-morbidities and less years of education -all these factor are proven to contribute to cognitive impairment in diabetes [1,6]. Decreased ghrelin levels could be another predictor of diagnosis of MCI in elderly diabetic population.…”
Section: Discussionmentioning
confidence: 99%
“…There is a high prevalence of mild cognitive impairment (MCI) in individuals with type 2 diabetes mellitus (T2DM) [1,2]. A meta-analysis of longitudinal studies reported that individuals with diabetes had 1.21-fold significantly increased odds of having Alzheimer's disease, 1.51-fold higher risk for any dementia and 1.21 higher risk for mild cognitive impairment compared to non-diabetic individuals [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Por otro lado, la educación superior condiciona un entrenamiento cognitivo mayor, lo que genera una mayor actividad sináptica. Consecuentemente, la falta de práctica de actividades mentales condiciona una carencia de entrenamiento y, por ende, resultados pobres en las pruebas relacionadas a la memoria 33,34 5,35 .Se propone que esta es la razón por la que su propia percepción ante la pérdida de memoria es mayor frente a la de las personas con edades inferiores a los 50 años y frente a los varones.…”
Section: Factores Asociados a La Auto-percepción De Pérdida De Memoriaunclassified